Theoretical analysis and application of immobilized methanotrophs as typical adsorbent materials for adsorption/degradation of trichloroethylene - Zhilin, Xing (Environmental technology, 2025)
Trichloroethylene (TCE) contamination presents a significant environmental challenge, necessitating efficient treatment solutions. This study aimed to develop an optimized immobilized bioreactor using methanotrophs for TCE degradation. Activated carbon fibres were identified as the optimal immobilization material, with an adsorption rate of 6-23 h - significantly faster than over 50 h for other materials - and the highest methane oxidation capacity of 0.970 mL·g-1·h-1. Adsorption kinetics indicated that activated carbon fibres followed a second-order kinetic model with a constant of 0.598 g·mg-1·h-1, suitable for low-concentration bacterial solutions. Thermodynamic analysis confirmed an exothermic process, favouring lower temperatures (288.15 K). The negative interaction energies, as per DLVO theory, suggested electrostatic attraction as a key mechanism. The bioreactor achieved 99% TCE removal within 1 h at an initial concentration of 10 mg·L-1, with visible microbial immobilization within 5 days. This research provides a novel and effective approach for using immobilized methane-oxidizing bacteria in TCE treatment, offering both theoretical and practical advancements for chlorinated hydrocarbon wastewater management